2018
DOI: 10.1016/j.scitotenv.2018.01.307
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling multiple pressures on fish assemblages in large rivers

Abstract: European large rivers are exposed to multiple human pressures and maintained as waterways for inland navigation. However, little is known on the dominance and interactions of multiple pressures in large rivers and in particular inland navigation has been ignored in multi-pressure analyzes so far. We determined the response of ten fish population metrics (FPM, related to densities of diagnostic guilds and biodiversity) to 11 prevailing pressures including navigation intensity at 76 sites in eight European large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 76 publications
(92 reference statements)
0
21
0
Order By: Relevance
“…Daufresne & Boët, 2007;Souchon & Tissot, 2012;Teletchea et al, 2009). However, other environmental changes are likely to have occurred locally over the same period and may also have contributed to the observed biological changes (Malmqvist & Rundle, 2002;Zajicek et al, 2018). However, other environmental changes are likely to have occurred locally over the same period and may also have contributed to the observed biological changes (Malmqvist & Rundle, 2002;Zajicek et al, 2018).…”
Section: Change In Species Composition and Poleward Shift Of Fish Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Daufresne & Boët, 2007;Souchon & Tissot, 2012;Teletchea et al, 2009). However, other environmental changes are likely to have occurred locally over the same period and may also have contributed to the observed biological changes (Malmqvist & Rundle, 2002;Zajicek et al, 2018). However, other environmental changes are likely to have occurred locally over the same period and may also have contributed to the observed biological changes (Malmqvist & Rundle, 2002;Zajicek et al, 2018).…”
Section: Change In Species Composition and Poleward Shift Of Fish Cmentioning
confidence: 99%
“…For all sites except for Civaux on the Vienne River, the number of newcomer species exceeded the number of species no longer present.4 | D ISCUSS I ON4.1 | General long-term changes and comparison with previously identified trendsLarge rivers have been undergoing multiple and profound environmental changes with direct and indirect, and possibly interacting effects on their biodiversity(Vörösmarty et al, 2010;Zajicek, Radinger, & Wolter, 2018). 18 in the 2010s;Figure 6a); over the same period, average cumulative abundance increased approximately four-fold (from an average 100 individuals per 20 min fishing in the 1980s to >400 in the 2010s;Figure 6b).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, examples of in-depth assessment of pressure effects, rehabilitation measures in or rehabilitation guidance for LFRs are rather scarce (e.g. Zajicek et al, 2018). Correspondingly, in Germany an analysis of the first river basin management plans implementing the European Water Framework Directive (WFD, 2000/60/EEC) revealed that huge knowledge gaps were evident (especially for large rivers), and mostly conceptual measures were planned (Kail and Wolter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional FRM also involves construction of extensive flood defence structures, such as in Rotterdam in the Netherlands, New Orleans in the United States and the Huai River in China, where main river channels have been isolated from their floodplains (Sayers et al 2013). This isolation profoundly affects fluvial processes and ecosystem functioning, and also eliminates or degrades the habitats required by many aquatic animals for foraging, refuge and reproduction (Bernhardt & Palmer 2007;Weber & Wolter 2016;Zajicek et al 2018).…”
Section: Introductionmentioning
confidence: 99%